Implementation of Behavioral Activation within a Care Pathway for Adolescent Depression at an Academic Medical Center. Issue 1 (2nd January 2023) - Lewandowski, R. Eric; Jenness, Jessica; Spiro, Carolyn; DeLonga, Kathryn; Crowe, Katherine; Tahilani, Kavita; Happer, Katie; Sullivan, Paul; Camacho, Kathleen; Kim, Jiyon; Fleiss, Karen; Schlechter, Alan; et al.
ABSTRACT: This paper describes the implementation of Behavioral Activation (BA) as the core psychotherapy treatment within a broader clinician-led effort to establish a care pathway for adolescent depression in an academic medical center that served public and private hospital systems. This quality improvement effort required a standardized yet flexible approach to psychotherapy to be used by clinicians with a range of experience and training backgrounds while serving diverse clinical populations in child psychiatry and pediatric clinics. This paper highlights implementation of BA in treating adolescent depression across these varying systems. In particular, the paper emphasizes the application of BA as a principle-driven, treatment that enables flexibility across settings while remaining rooted in scientific evidence. The paper also reviews lessons learned from this effort that may support efforts to implement BA in other clinical settings and systems.